Effect of tobacco use and nicotine dependence on the quality of sleep among tuberculosis patients: A cross-sectional study - Tukaram Kendre; Rajat Mishra; Priyanka Guha; Gulshan Singh Rana; Krishna Pandey; Sameer Dhingra (Clinical Epidemiology and Global Health, 2025)
Background: To enhance the treatment outcomes of tuberculosis (TB), it is crucial to understand the sleep quality of patients who use tobacco. This study seeks to measure the level of nicotine dependence in tuberculosis patients who use tobacco and its correlation to sleep quality. Additionally, it aims to examine the extent to which tobacco use affects the sleep quality of TB patients. Methods: A cross-sectional study was conducted at a TB centre in Patna, Bihar, India with n = 209 patients. The study used the Pittsburgh Sleep Quality Index questionnaire to measure sleep quality, and the Fagerström Test for Nicotine Dependence, as well as the Fagerström Test for Nicotine Dependence-Smokeless Tobacco questionnaires, to evaluate the level of nicotine dependence. Results: The study revealed that TB patients with tobacco use reported significantly worse sleep quality (86.1 %, 95 % CI: 80.6–91.1) compared to non-tobacco users (13.9 %, 95 % CI: 9.4–19.4). Additionally, the study identified a correlation between nicotine dependence (Smokers r = .550, p < .001 and smokeless tobacco r = .835, p < .001) and poor sleep quality. Smokers are (β = 2.250, 95 % CI: 1.380–3.120, p < .001) more prone to experience poorer sleep quality compared to non-smokers, while users of smokeless tobacco are (β = 5.167, 95 % CI: 4.465–5.869, p < .001) more prone to experience worse sleep quality compared to non-users of smokeless tobacco. Conclusion: The study concluded that tuberculosis patients with tobacco use experienced poorer sleep quality. Improving sleep quality could enhance the overall management and care for individuals with tobacco-associated tuberculosis, leading to better health outcomes.